Exploring new technologies for seated anthropometry (Human Factors in Design, 2021)
Due to the greater complexity of obtaining digital anthropometric data from seated individuals, there is a gap in the scientific literature about this. Thus, this study investigated strategies for collecting data from seated subjects through three-dimensional scanning. A scanning system was proposed with the use of a transparent support. The use of this system was analyzed with five subjects in the sitting position. This exploratory study made it possible to raise the necessary variables for the design requirements of a seated digital scanning system applicable to anthropometry and the development of adapted products.